Whither parliamentary privileges? - Agnihotri, Vivek K. (The Journal of Governance)
Through a Parliamentary Bulletin issued by the Rajya Sabha Secretariat on February 18, 2023 the Members were informed that the Chairman, Rajya Sabha has referred a question of alleged breach of privilege arising out of gross disorderly conduct displayed by 12 Members of Rajya Sabha in violation of rules and etiquette of Rajya Sabha by repeatedly entering the well of the Council, shouting slogans and persistently and wilfully obstructing the proceedings of the Council, compelling the Chair to repeatedly adjourn the sittings of the Council. The reference was made under rule 203 of the Rules of Procedure and Conduct of Business (Rules, for short) of the Rajya Sabha to the Committee of Privileges (CoP, for short) for examination, investigation and report.- Reproduced